The Role of Buying Decisions on Electronic Word of Mouth and Loyalty Mediated Customer Prices as Intervening Variables - Muhammad Arif (Journal of International Conference Proceedings (JICP), 2022)
The purpose of this study was to determine and analyze the influence of Electronic Word of Mouth and Price on the Buying Decision of Medan City Food, Customer Loyalty as an Intervening Variable, directly or indirectly. The approach used in this study is an associative approach. The population in this study were all the people of Medan City who had purchased Medan culinary specialties. While the sample in this study were 100 people. Data collection techniques in this study used interview techniques, study documentation, observation, and questionnaires. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that Electronic Word of Mouth and Price directly have a positive and significant effect on Buying Decisions for Medan City Foods, Customer Loyalty as an Intervening Variable. In other words, Customer Loyalty does act as a mediator. Keywords: Electronic Word Of Mouth, Price, Buying Decision, Customer Loyalty.